Resultados clínicos e avaliação da resistência insulínica com abreviação do jejum pré-operatório em pacientes submetidos à revascularização do miocárdio com circulação extracorpórea: estudo randomizado duplo-cego. - Feguri, Gibran Roder (2012)
Multimodal protocols, when used, enhance several perioperative clinical variables. Limited information is available about the reduction of preoperative fasting with administration of clear liquids enriched with carbohydrate in cardiovascular surgeries. Objectives: To evaluate clinical and metabolic variables, also security using fasting abbreviation with drinks containing carbohydrates in patients undergoing coronary artery bypass graft surgery with cardiopulmonary bypass. Casuistic and Methods: Prospective study with 40 patients randomized into two groups: 20 patients (Group I) undergoing abbreviated fasting with the use of maltodextrin at 12.5%, 6h and 2h before anesthetic induction; 20 patients (Group II) undergoing abbreviated fasting with water, in the same way. Preoperative discomfort and thirst, bronchoaspiration in the anesthetic induction, postoperative nausea and vomiting, and also clinic variables and surgical morbimortality during hospitalization were evaluated. Insulin resistance was evaluated by Homa-RI index and also by the need of exogenous insulin during perioperative phase. Pancreatic beta-cell excretory function was evaluated by Homa-Beta index and glucose control by tests of capillary glucose. The mean age was 56.6±6years for Group I and 60.5±7years for Group II; also with 14 male patients in Group I and 12 male patients in Group II (P>0.05). Risk factors for coronary artery disease and clinic characteristics were equitable among groups. The mean of left ventricle ejection fraction was 53.2±11.9% for Group I and 49.8±13.1% for Group II (P=0.440). Results: Deaths, mediastinitis, stroke, or perioperative acute myocardial infarction did not occur. No case of bronchoaspiration occurred in the anesthetic induction. Postoperative nausea and vomiting incidence was similar among groups. Postoperative atrial fibrillation occurred in two patients of each group and infectious complications did not differ among groups (P=0.611). Patients of Group I presented, in average, two days less of hospital stay (P=0.025) and one day less in the ICU (P<0.001). The time for weaning (withdrawal) of vasoactive amine in the ICU was lower for Group I (P=0.034). Glycemic control, in the six first hours of ICU recovery, was worse for Group II (P=0.012). Results of serial glycemia did not differ among groups. Insulin resistance was detected and did not differ among groups (P>0.05). Decline of pancreatic beta-cell excretory function was observed in both groups (P<0.001). Conclusion: Preoperative fasting abbreviation with carbohydrates for coronary artery bypass graft surgery is safe and could be performed. The glycemic control improved in the first six hours of ICU recovery; the length of ICU and hospital stay decreased and there was less time in the use of vasoactive amine. However, neither insulin resistance nor morbimortality during hospital phase were influenced.